The psychology of offensive and defensive intergroup violence: Preregistered insights from 58 countries - Jonas R. Kunst; Tomasz Besta; Michał Jaśkiewicz; Anna Natalia Gajda; Markus Sanden; Mina Marie Flatebø; Sulaiman Olanrewaju Adebayo; Marios Adonis; Collins Badu Agyemang; Raymond Agyenim Boateng; Serap Arslan Akfirat; Samir Al-adawi; et al. (Proceedings of the National Academy of Sciences, 2026)
Evolutionary theory and historical evidence suggest humans possess distinct psychological tendencies for defensive and offensive violence, which have insufficiently been considered in research. In a large-scale preregistered study across 58 countries ( N = 18,128), we demonstrate that violent extremist intentions manifest along two distinct psychological phenomena: defensive extremism, motivated by protecting one’s group from (perceived) threats, and offensive extremism, driven by establishing group dominance. We show that these dimensions a) can be reliably differentiated across diverse cultural contexts, b) are distinctively associated with psychological dispositions, and c) systematically differentiate countries varying in macrolevel sociopolitical functioning and violence. Across nations, a two-factorial structure was observed that was invariant at the scalar level. Defensive extremist intentions were consistently higher than offensive extremism in 56 out of 58 countries, suggesting greater moral acceptance of protective violence. While psychopathy was positively related to both types of violent extremist intentions, those high in Machiavellianism and narcissism demonstrated particularly higher levels of defensive extremist intentions. By contrast, those scoring high on religious fundamentalism and social dominance orientation demonstrated particularly higher levels of offensive extremist intentions. Unexpectedly, liberal political group identification was associated with higher offensive but lower defensive extremist intentions. Crucially, offensive (but not defensive) intentions were associated with macrolevel societal dysfunction, including political terror and internal conflict. These findings establish that defensive and offensive violent extremist intentions represent two conceptually different forms of extremism across a large and diverse range of countries, with consequences for research and practice.